Mapping evidence on the distribution of uterine fibroids in sub-Saharan Africa: A scoping review protocol. - Vuyisile Ginindza; Makandwe Nyirenda; Mbuzeleni Hlongwa; Themba G Ginindza (PLoS ONE)
Background Uterine fibroids are the most common pelvic benign tumours found in reproductive-aged women and may affect up to 70% of all women by menopause. Uterine fibroids place a heavy burden on women and society resulting in poor quality of life, impaired self-image, and impaired social, sexual, emotional, and physical well-being of affected individuals. Aim This study aims to map the evidence on the burden of uterine fibroids in Sub-Saharan Africa; uterine fibroids' burden by age, uterine fibroids' geographic burden, uterine fibroids' cost estimation and reported experiences among women diagnosed with uterine fibroids. Setting Articles will be selected from countries within Sub-Saharan Africa. Methods and analysis This scoping review will be guided by the Arksey & O'Malley framework, enhanced by Levac et al (2010). The following electronic databases will be searched; PubMed, EBSCOhost (Cumulated Index to Nursing and Allied Health Literature and Health Source), Medical Literature Analysis and Retrieval System Online, Cochrane Library, Scopus, Web of Science, Africa Journal Online, and Google Scholar. The Population Concept and Context (PCC) framework will be used and the PRISMA flow diagram will also be used to show the literature search and selection of studies. Descriptive data analysis will be used; results will be presented in themes, narrative summaries, tables, and charts. Discussion The study anticipates finding relevant literature on the distribution of uterine fibroids, the burden of uterine fibroids in terms of geographic distribution, age distribution, and cost approximation related to the disease. This will assist in identifying research gaps to guide future research contribute to the body of scientific knowledge and develop preventative strategies for the disease.